Rural Non-Agricultural Employment in India: Role of Development Process and Rural-Urban Employment Linkages - Planning Commission (Planning Commission Government of India, 1996)
The study Rural Non-Agricultural Employment in India: Role of Development Process and Rural-Urban Employment Linkages by D.N. Basu and S.P. Kashyap examines the rising trend and implications of non-agricultural employment (NFE) in rural India between 1961 and 1983. The research highlights a shift in the rural workforce, with male non-agricultural participation increasing from 16.3% to 22.4%, accompanied by significant regional disparities—ranging from under 10% in Madhya Pradesh and Rajasthan to about 40% in Kerala. The growth in NFE is largely driven by population pressure, stagnant agricultural yields, and labor absorption constraints, often reflecting a mix of distress-driven diversification and necessary income supplementation. NFE is characterized by informal, semipermanent, and casual labor, frequently supplementing agricultural income, while rural-urban linkages through seasonal migration illustrate the integration of rural labor into urban economies. The study underscores the importance of region-specific policies and micro-level research to enhance agricultural productivity, support stable non-farm employment, and alleviate rural poverty. By emphasizing the interplay of rural labor dynamics, agricultural limitations, and migration patterns, the study provides critical insights for fostering sustainable socioeconomic stability and targeted rural development strategies.
Government of India Planning Commission
Keywords: Rural Employment; Non-Agricultural Employment; Occupational Diversification; Agricultural Productivity; Rural Poverty; Casual Labor; Rural-Urban Linkages; Migration Patterns; Informal Sector; Regional Disparities; Policy Implications; Socioeconomic Stability